1993
DOI: 10.1007/bf01955157
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 is a Cyclosporin A binding protein

Abstract: Inflammatory immune reactions occur during transplant rejections and autoimmune diseases. Such reactions are mediated by cytokines, including interleukin-8 (IL-8). Cyclosporin A (CsA) exerts immunosuppressive activities by binding to immunoregulatory proteins termed cyclophilins. The anti-inflammatory effects of CsA are still not fully understood. Searching for novel neutrophil-activating proteins, we observed that an antiserum against human recombinant Interleukin-8 (IL-8) cross-reacted with cyclophilins in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
7
2
Order By: Relevance
“…Interestingly, a direct interaction of CsA or its analogues with different cellular proteins, including plasma membrane proteins, has been demonstrated [20][21][22]37,38]. This possibility is not evident, however, from the in vivo data provided in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…Interestingly, a direct interaction of CsA or its analogues with different cellular proteins, including plasma membrane proteins, has been demonstrated [20][21][22]37,38]. This possibility is not evident, however, from the in vivo data provided in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…7,25,26 It has been demonstrated that CsA inhibits lymphocyte chemotaxis 27 and pulmonary recruitment of inflammatory leukocytes 5 and that interleukin-8-a chemokine that recruits and activates neutrophils-is a cyclosporin A binding protein. 28 Furthermore the cyclosporin binding proteins or cyclophilins are chemotactic for eosinophils and neutrophils 29 and their chemotactic activity is inhibited by CsA. 29 Therefore it seems that CsA modulates chemotaxis.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a direct interaction of CsA or its analogues with different cellular proteins, including plasma membrane proteins, has been demonstrated [20][21][22]37,38]. Interestingly, a direct interaction of CsA or its analogues with different cellular proteins, including plasma membrane proteins, has been demonstrated [20][21][22]37,38].…”
Section: Discussionmentioning
confidence: 99%